Service skills in solving hotel guest problems in the food and beverage service department in the post-COVID-19 pandemic in the hospitality world - Rachma Hani Rahayuning Safitri; Oktavia Ayu Fadilah; Veronica Halim (Surya Hijau Manfaat, 2023)
Hotels have many departments, one of which is food and beverage service, in which the role of the waiter influences the hotel's image in many ways. One of them bridges between guests and waiters. In this case, we need good communication skills when serving guests, as well as dealing with guest complaints by using good and correct communication. The goals given are being able to hone communication skills when dealing with guest problems with Food and Beverages Service. This study applies a qualitative method design, collecting observations on data and literature studies. Based on this research, there are two findings of problems related to communication skills in the hotel sector. The first is how to improve the handling of guest service complaints at hotels and the second is how to overcome obstacles when serving guests during a pandemic. In this article, we explain about Food and Beverage Service. The author applies it to learning in improving communication and problem solving to broaden our understanding, so that we can learn freely and carefully in using standard procedures in hotels and personal quality values, as well as barriers caused by a lack of communication skills in solving problems with guests due to service which is less than perfect.